Certolizumab pegol in the treatment of spondyloarthritis - Mariusz Korkosz (Rheumatology, 2014)
Spondyloarthropaties (SpA) are a second common group of inflammatory rheumatic diseases after systemic connective tissue diseases. They are a frequent cause of disability. Tumor necrosis factor α (TNF-α) plays a crucial role in the initiation and continuation of chronic inflammation in SpA patients. Therefore, in case of high disease activity, despite treatment with non-steroidal anti-inflammatory drugs and/or synthetic disease modifying antirheumatic drugs, treatment with biologics is very efficacious. Certolizumab pegol is a one of the TNF inhibitors, with proven efficacy in the treatment of active SpA. This article summarizes basic data on certolizumab pegol, and results of clinical trials applied for the drug registration for the use in the management of patients with active SpA.